Therapeutic exercise protocol for the prevention of anterior cruciate ligament injuries in female soccer players with dynamic knee valgus (RCT) - Amanda Coves García; Emilio José Poveda Pagán (Trials)
Abstract Background Women’s football has experienced exponential growth over the last 10 years. Its popularity is associated with an increase in ACL injuries. They constitute a major current problem as they account for 43% of the injury burden during the sports season. Despite the existing training programs, no uniform criteria have been established to design a precise intervention protocol, with specific tasks linked to women’s football, nor has it been proposed to optimize the current programs. Methods Randomized, double-blind, single-center clinical trial protocol scheduled for the 2025–2026 women’s football season. There will be 2 groups: a group that will follow a specific ACL injury prevention protocol and a control group. The intervention period will last 12 weeks. Measurements will be taken at 3 time points. The biomechanics of the lower limbs, the jump-landing dynamics, and the pre- and post-training satisfaction of the players will be evaluated. Image capture and processing systems will be used as well as tests such as the DVJ and the LESS scoring system, among others. Discussion This protocol aims to be one of the first to implement an ACL injury prevention program for women footballers with DKV. Despite the scarcity of research in this area, studies support beneficial effects at a preventive level. Trial registration ClinicalTrials.gov NCT06083818. Registered on 03 October 2023.